O Ensaísmo na Historiografia Brasileira - Mendes, Claudinei Magno Magre [UNESP] (Universidade Estadual de Maringa, 2012)
In this paper we analyze the question of character essayistic the historiography of the first half of the twentieth century. We examined this issue due to the emergence of a new trend on the historiographical colonization (School of Rio) who criticizes, among other things, the essay-like character in historiography. Whereas the criticism expressed how a new trend breaks with the existing historiography, we decided to examine this critical gauge. To promote the overcoming of a certain history is necessary to understand it in its historicity, that is, the motivations that led historians to examine the history of a given way. Of course, criticism is a moment of transcendence. But to be a radical departure is necessary to understand the historiography of historical criticism and not simply point their supposed mistakes, shortcomings and failures.

Neste texto analisamos a questão do caráter ensaístico da historiografia brasileira da primeira metade do século XX. Examinamos esta questão em função do surgimento de uma nova tendência historiográfica relativa à colonização (Escola do Rio) que critica, dentre outros aspectos, o caráter ensaístico da historiografia. Considerando que a crítica expressa o modo como uma nova tendência rompe com a historiografia vigente, resolvemos examinar essa crítica para avaliar sua extensão. Para se promover a superação de determinada historiografia, é necessário compreendê-la em sua historicidade, isto é, as motivações que levaram historiadores a examinar a história de determinada maneira. Evidentemente, a crítica constitui um momento dessa superação. Mas, para haver uma ruptura radical, é necessária a compreensão histórica da historiografia criticada e não simplesmente a indicação de supostos equívocos, deficiências e falhas.
The question of the essays in brazilian historiography
Keywords: Brazilian historiography; Essay; Colonization; School of Rio; Historiografia brasileira; Ensaio; Colonização; Escola do Rio